Penerapan Kekayaan Media Tentang Pemberitaan Unggahan Terkait Raperda APBD Tahun 2020-2023 Oleh Humas pada Instagram DPRD Kota Surakarta - Olivia Murlitta; Rahmat Wisudawanto; Hasbullah Azis (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The Public Relations of the Surakarta DPRD disseminates information related to the upload of the draft regional regulation (Raperda) of the APBD via Instagram. In disseminating information via Instagram, public relations utilizes Instagram features, namely photos, captions, hashtags, links, and mentions that can invite responses from followers. The study aims to assess the extent to which the Instagram uploads of the Surakarta DPRD meet the criteria for media richness which include immediacy, diversity of signs, language variation and personal sources based on the Media Richness theory by Daft and Lengel (1984). This study is a qualitative descriptive study with primary data sources uploaded on the Instagram account @dprdkotasurakarta and secondary data from relevant journal articles. The sampling technique used total sampling. This study used data collection techniques, namely observation and documentation. The application of media richness by the Surakarta DPRD public relations has great potential in conveying information quickly and effectively. However, several aspects need to be improved to optimize the effectiveness of messages conveyed to the public which have been proven through a SWOT analysis. SWOT analysis identifies the strengths, weaknesses, opportunities, and threats of each unsurt which shows that Instagram has implemented media richness.